A carbon-based composite material and a preparation method thereof, and a device for mobile capacitor deionization coupled electrochemical denitrification and a method of using the device

By using carbon-based composite materials, including activated carbon and Cu2Te/MgAl-LDH heterojunction in electrochemical denitrification devices, the problem of low efficiency in removing nitr nitrogen in electrochemical reduction is solved, and efficient harmless conversion of nitr nitrogen and N2 selective generation is achieved.

CN118878065BActive Publication Date: 2025-03-28XIAMEN OCEAN VOCATIONAL & TECH COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411216948.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-03-28
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove the accumulation of nitr nitrogen in factory circulating water aquaculture systems, especially in the case of interference ion influence, electrostatic repulsion on the electrode surface and poor electrocatalyst selectivity, and the application of electrochemical reduction nitr nitrogen technology is limited.

Method used

Carbon-based composite materials, including activated carbon and Cu2Te/MgAl-LDH heterojunctions loaded on activated carbon, are used for flow capacitance deionized electrochemical denitrification devices. The composite material achieves efficient removal of NO3- and selective generation of N2 through selective adsorption and interface effect regulation of Cu2Te/MgAl-LDH heterojunction.

Benefits of technology

Efficient harmless conversion of nitr nitrogen was achieved, the removal rate of NO3- remained above 93%, and the selectivity of N2 was maintained above 96%, which significantly improved the effect of nitr nitrogen treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118878065B_ABST
    Figure CN118878065B_ABST
Patent Text Reader

Abstract

The present invention provides a carbon-based composite material and a preparation method thereof, and a mobile capacitor deionization coupled electrochemical denitrification device and a use method thereof, belonging to the technical field of water treatment. The carbon-based composite material provided by the present invention uses activated carbon as a carrier, which is beneficial to improve the Cu 2 Dispersibility of Te / MgAl-LDH heterojunction; The carbon-based composite material provided by the present invention includes Cu 2 Te / MgAl‑LDH heterojunction can regulate Cu by using interface effect 2 Te electronic structure, adsorption energy, and regulation of the optimal intermediate product adsorption energy; when this carbon-based composite material is used in mobile capacitor deionization coupled electrochemical denitrification, it can react with NO 3 ‑ Intercalation reaction occurs to achieve selective adsorption of NO 3 ‑ , preventing anions (Cl ‑ 、SO 4 2‑ competitive adsorption of N 2 , thereby being able to efficiently achieve harmless conversion of nitrate-nitrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a carbon-based composite material and a preparation method thereof, and a mobile capacitor deionization coupled electrochemical denitrification device and a use method thereof. Background Art

[0002] The accumulation of nitrate-nitrogen in factory-scale recirculating aquaculture systems (RAS) is one of the important environmental problems, and it is particularly important to achieve harmless conversion of nitrate-nitrogen. At present, the main treatment methods for harmless conversion of nitrate-nitrogen include: ion exchange, reverse osmosis, biological denitrification, catalytic hydrogenation and electrochemical reduction. Electrochemical reduction of nitrate-nitrogen technology (NO3RR) has the advantages of high removal efficiency, mild operating conditions, controllable target product selectivity, and environmental friendliness, and has gradually become a research hotspot. However, the influence of interfering ions, the electrostatic repulsion on the electrode surface, and the poor selectivity of electrocatalysts have seriously restricted the efficient removal of nitrate-nitrogen by electrochemical reduction of nitrate-nitrogen technology and its application in RAS. Therefore, designing the corresponding hardness ion removal process and high-performance electrocatalyst is of great significance for the development of efficient removal of NO3 - The RAS water purification system is of great significance.

[0003] Flowing capacitor deionization (FCDI) technology is an emerging electrosorption water treatment technology. The basic principle of FCDI technology is to form an electrostatic field between the electrodes by applying voltage or current to the cathode and anode. The charged ions or particles move to the electrode chamber with opposite charge due to the electrostatic force in the electrostatic field and are finally adsorbed on the surface of the current collecting plate or electrode particles to form a double layer and stored therein. This electrosorption process of removing ions from water is highly efficient, fast, energy-saving and environmentally friendly, providing the possibility of removing interfering ions. However, for wastewater containing ammonia nitrogen, ammonia nitrogen in water refers to a nitrogen-containing oxygen-consuming compound, mainly in the form of free ammonia (NH3) and ammonium ions (NH4 + ) form. When using FCDI technology to treat ammonia nitrogen-containing wastewater, traditional carbon materials have a high affinity for NH4 + Poor adsorption performance leads to NH4 in the influent + After electromigration to the flow electrode chamber, NH4 + It will be enriched in the flowing electrode liquid, thus greatly increasing the NH4 in the flowing electrode + concentration, further leading to NH4 + Back diffusion occurs, which ultimately leads to a decrease in the performance of the FCDI process and unsatisfactory ammonia nitrogen removal effect. In addition, when NO3RR is directly coupled with FCDI, the competitive adsorption problem of coexisting anions on the electrode surface has not been solved, making it difficult to achieve efficient and harmless conversion of nitrate nitrogen by coupling NO3RR with FCDI.

[0004] Therefore, there is an urgent need to provide a carbon composite material that can be used in a mobile capacitive deionization coupled electrochemical denitrification device to achieve efficient and harmless conversion of nitric nitrogen. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon-based composite material and a preparation method thereof, a device for mobile capacitor deionization coupled electrochemical denitrification and a method of using the same. When the carbon-based composite material provided by the present invention is used as a carbon composite material for a mobile capacitor deionization coupled electrochemical denitrification device, it can efficiently achieve harmless conversion of nitric nitrogen.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a carbon-based composite material, comprising activated carbon and a Cu2Te / MgAl-LDH heterojunction supported on the activated carbon, wherein the molar ratio of Mg to Al in the Cu2Te / MgAl-LDH heterojunction is 1-5:1.

[0008] Preferably, the mass of the Cu2Te / MgAl-LDH heterojunction accounts for 1-5% of the mass of the carbon-based composite material.

[0009] Preferably, the mass ratio of Cu2Te to MgAl-LDH in the Cu2Te / MgAl-LDH heterojunction is (1-2):(1-5).

[0010] The present invention also provides a method for preparing the carbon-based composite material described in the above technical solution, comprising the following steps:

[0011] (1) mixing a soluble aluminum salt, water and ethanol to obtain a soluble aluminum salt solution;

[0012] (2) mixing activated carbon, soluble magnesium salt, urea and the soluble aluminum salt solution obtained in step (1) and then impregnating the mixture to obtain a solid-liquid mixture; the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution is 1 to 5:1;

[0013] (3) subjecting the solid-liquid mixture obtained in step (2) to a hydrothermal reaction to obtain a MgAl-LDH@HPWC composite material;

[0014] (4) mixing the MgAl-LDH@HPWC composite material obtained in step (3) with ethylene glycol, an alkaline regulator, tellurium dioxide, a stabilizer and a reducing agent, and performing a reduction reaction to obtain a Te nanosheet / MgAl-LDH@HPWC mixed solution;

[0015] (5) The Te nanosheet / MgAl-LDH@HPWC mixed solution obtained in step (4) is mixed with a soluble copper salt solution to perform a solvothermal reaction to obtain a carbon-based composite material.

[0016] Preferably, the temperature of the hydrothermal reaction in step (3) is 80 to 150° C., and the time of the hydrothermal reaction is 16 to 30 hours.

[0017] Preferably, the temperature of the reduction reaction in step (4) and the solvothermal reaction in step (5) are independently 120 to 200° C.; and the time of the reduction reaction and the solvothermal reaction are independently 30 to 90 min.

[0018] The present invention also provides a device for mobile capacitive deionization coupled electrochemical denitrification, comprising a mobile electrode, a cation exchange membrane, a reaction chamber, an anion exchange membrane and a carbon-based fixed electrode which are sequentially arranged in contact;

[0019] The carbon-based fixed electrode is the carbon-based composite material described in the above technical solution or the carbon-based composite material prepared by the preparation method described in the above technical solution;

[0020] A serpentine flow channel is engraved on the side of the electrode cavity of the flow electrode that contacts the cation exchange membrane; a liquid inlet and a liquid outlet are provided on the electrode cavity, and the liquid inlet and the liquid outlet are respectively arranged at two ends of the serpentine flow channel;

[0021] The reaction chamber is a silica gel plate with serpentine hollowing; the serpentine hollowing coincides with the projection of the serpentine flow channel in the electrode chamber on the cation exchange membrane; the space formed by the serpentine hollowing, the cation exchange membrane and the anion exchange membrane is a reaction chamber; a water inlet and a water outlet are provided on the reaction chamber; the water inlet is arranged at one end of the serpentine hollowing corresponding to the liquid inlet; the water outlet is arranged at one end of the serpentine hollowing corresponding to the liquid outlet; the reaction chamber includes a through hole with a nut.

[0022] Preferably, the length of the electrode cavity is 80-200 mm, the width of the electrode cavity is 50-120 mm, and the thickness of the electrode cavity is 5-15 mm.

[0023] Preferably, the depth of the serpentine flow channel is 1-3 mm, the width of the serpentine flow channel is 1-3 mm, and the number of columns of the serpentine flow channel is 15-35.

[0024] The present invention also provides a method for flow capacitor deionization coupled electrochemical denitrification, using the device described in the above technical solution, comprising the following steps:

[0025] Passing the liquid electrode material into the serpentine flow channel of the electrode cavity through the liquid inlet to form a flow electrode;

[0026] The mobile electrode is connected to the negative electrode of the external power supply, and the fixed electrode is connected to the positive electrode of the external power supply to obtain a FCDI system;

[0027] The wastewater to be treated is introduced into the reaction chamber from the water inlet and flows out from the water outlet, and the FCDI process is circulated until the total nitrogen content in the treated wastewater reaches the standard, then the introduction of the wastewater to be treated is stopped, and the remaining wastewater in the reaction chamber is retained;

[0028] Switching the positive and negative electrodes of the external power supply, connecting the mobile electrode to the positive electrode of the external power supply and connecting the fixed electrode to the negative electrode of the external power supply, thereby obtaining a NO3RR system;

[0029] The through hole of the reaction chamber is opened, and the remaining wastewater is subjected to an electrochemical reduction reaction in the NO3RR system until no gas is generated.

[0030] The present invention provides a carbon-based composite material, comprising activated carbon and a Cu2Te / MgAl-LDH heterojunction loaded on the activated carbon, wherein the molar ratio of Mg to Al in the Cu2Te / MgAl-LDH heterojunction is 1 to 5:1. The carbon-based composite material provided by the present invention uses activated carbon as a carrier, and the activated carbon has a three-dimensional porous structure, which is beneficial to improving the dispersibility of the Cu2Te / MgAl-LDH heterojunction; and when the carbon-based composite material is used for flow capacitor deionization coupled electrochemical denitrification, it can reduce NO3 - The diffusion distance on the cathode reduces the resistance of water flow and increases the NO3 - The carbon-based composite material provided by the present invention comprises a Cu2Te / MgAl-LDH heterojunction, wherein MgAl-LDH is a magnesium-aluminum hydrotalcite, and the interlayer spacing of the magnesium-aluminum hydrotalcite is different when the molar ratio of Mg to Al is different. When the molar ratio of Mg to Al is 1 to 5:1, it has a suitable interlayer spacing. When the carbon-based composite material is used for flow capacitor deionization coupled electrochemical denitrification, it can react with NO3 - Intercalation reaction occurs to achieve selective adsorption of NO3 - , preventing anions (Cl - 、SO4 2-The carbon-based composite material provided by the present invention has a Cu2Te / MgAl-LDH heterojunction, which can use the interface effect to regulate the electronic structure and adsorption energy of Cu2Te, and regulate the optimal intermediate product adsorption energy. When the carbon-based composite material is used for flow capacitor deionization coupled electrochemical denitrification, it can achieve selective production of N2, and thus can efficiently achieve harmless conversion of nitrate and nitrogen. The results of the embodiment show that after the carbon-based composite material provided by the present invention is used as the fixed electrode of the flow capacitor deionization coupled electrochemical denitrification device, after running for 50 minutes, NO3 - The removal rate can be maintained above 93%, and the N2 selectivity can be maintained above 96%, which can efficiently achieve harmless conversion of nitric nitrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of a method for preparing a carbon-based composite material in an embodiment of the present invention;

[0032] Figure 2 It is a schematic diagram of an explosion of a device for mobile capacitor deionization coupled with electrochemical denitrification according to an embodiment of the present invention;

[0033] Figure 3 Schematic diagram of the principle of the method of mobile capacitor deionization coupled electrochemical denitrification in an embodiment of the present invention;

[0034] Figure 4 XRD patterns of HPWC and MgAl-LDH@HPWC prepared in Examples 1 to 5 of the present invention;

[0035] Figure 5 SEM images of MgAl-LDH@HPWC and HPWC prepared in Example 1 of the present invention;

[0036] Figure 6 HRTEM image of MgAl-LDH@HPWC prepared in Example 1 of the present invention;

[0037] Figure 7 Method NO3 provided by Examples 7 to 11 and Comparative Examples 1 to 10 of the present invention - Removal rate result diagram;

[0038] Figure 8 The selectivity result diagram of method N2 provided in Examples 7 to 11 of the present invention and Comparative Examples 1 to 10. DETAILED DESCRIPTION

[0039] The invention provides a carbon-based composite material, comprising activated carbon and a Cu2Te / MgAl-LDH heterojunction loaded on the activated carbon.

[0040] The carbon-based composite material provided by the invention comprises activated carbon.

[0041] In the present invention, the activated carbon is preferably wood activated carbon. The wood activated carbon used in the present invention has a three-dimensional porous structure, which can make the Cu2Te / MgAl-LDH heterojunction distribution more uniform.

[0042] In the present invention, the thickness of the wood activated carbon is preferably 0.5-2 mm, more preferably 1 mm, and the pore structure preferably includes macropores and small pores, the pore size of the macropores is preferably 100-200 μm, more preferably 150-200 μm; the pore size of the small pores is preferably 0-10 μm, more preferably 5-10 μm. In the present invention, when the activated carbon is of the above type, it can reduce the diffusion distance of ions and the resistance of the fluid during use, thereby facilitating the increase of the contact area with the ions and offsetting the hindrance of electrostatic repulsion.

[0043] The carbon-based composite material provided by the present invention comprises a Cu2Te / MgAl-LDH heterojunction supported on the activated carbon. In the present invention, the molar ratio of Mg to Al in the Cu2Te / MgAl-LDH heterojunction is 1 to 5:1, preferably 2 to 3:1. When the molar ratio of Mg to Al in the Cu2Te / MgAl-LDH heterojunction is controlled within the above range, the MgAl-LDH can have a suitable interlayer spacing and selectively adsorb NO3 - When the carbon-based composite material is used as the fixed electrode of the mobile capacitive deionization coupled electrochemical denitrification device, it is beneficial to intercalate with NO3- to achieve selective adsorption and prevent anions (Cl-, SO4 2- etc.) competitive adsorption.

[0044] In the present invention, the mass of the Cu2Te / MgAl-LDH heterojunction accounts for 1-5% of the mass of the carbon-based composite material, and more preferably 2-3%. The present invention controls the percentage of the mass of the Cu2Te / MgAl-LDH heterojunction to the mass of the carbon-based composite material within the above range, which is more conducive to exerting the role of the Cu2Te / MgAl-LDH heterojunction.

[0045] In the present invention, the mass ratio of Cu2Te and MgAl-LDH in the Cu2Te / MgAl-LDH heterojunction is preferably (1-2): (1-5), and more preferably (1-2): (1-3). When the present invention controls the mass ratio of the two within the above range, it is more conducive to utilizing the interface effect to regulate the electronic structure and adsorption energy of Cu2Te, so that the carbon-based composite material can selectively produce N2 when used as a fixed electrode of a mobile capacitive deionization coupled electrochemical denitrification device.

[0046] The carbon-based composite material provided by the present invention uses activated carbon as a carrier and has porosity, which is more conducive to improving the dispersibility and loading amount of the Cu2Te / MgAl-LDH heterojunction; the present invention controls the interlayer spacing of the magnesium-aluminum hydrotalcite by controlling the molar ratio of Mg and Al in MgAl-LDH, so that it can selectively adsorb NO3 - The present invention utilizes the interface effect to regulate the electronic structure and adsorption energy of Cu2Te and regulates the adsorption energy of the carbon-based composite material.

[0047] The present invention also provides a method for preparing a carbon-based composite material, comprising the following steps:

[0048] (1) mixing a soluble aluminum salt, water and ethanol to obtain a soluble aluminum salt solution;

[0049] (2) mixing activated carbon, soluble magnesium salt, urea and the soluble aluminum salt solution obtained in step (1) and then impregnating the mixture to obtain a solid-liquid mixture; the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution is 1 to 5:1;

[0050] (3) subjecting the solid-liquid mixture obtained in step (2) to a hydrothermal reaction to obtain a MgAl-LDH@HPWC composite material;

[0051] (4) mixing the MgAl-LDH@HPWC composite material obtained in step (3) with ethylene glycol, an alkaline regulator, tellurium dioxide, a stabilizer and a reducing agent, and performing a reduction reaction to obtain a Te nanosheet / MgAl-LDH@HPWC mixed solution;

[0052] (5) The Te nanosheet / MgAl-LDH@HPWC mixed solution obtained in step (4) is mixed with a soluble copper salt solution to perform a solvothermal reaction to obtain a carbon-based composite material.

[0053] The invention mixes soluble aluminum salt, water and ethanol to obtain a soluble aluminum salt solution.

[0054] In the present invention, the soluble aluminum salt preferably includes aluminum nitrate, aluminum sulfate or aluminum trichloride. The present invention utilizes the above soluble aluminum salt to provide an aluminum source for MgAl-LDH.

[0055] In the present invention, the water and ethanol are used as a mixed solvent. The present invention uses water and ethanol as a mixed solvent. Ethanol can reduce the surface tension of the solution and help disperse the nanoparticles; ethanol can also affect the reaction kinetics, and accelerate or slow down the reaction rate by changing the dielectric constant and polarity of the solvent, thereby affecting the crystallization process of MgAl-LDH and the purity of the final product. In the present invention, the volume ratio of water and ethanol is preferably (1 to 6): 1, and more preferably 4: 1. The present invention controls the volume ratio of water and ethanol within the above range, which is more conducive to obtaining MgAl-LDH with better dispersibility and higher purity.

[0056] In the present invention, the concentration of aluminum ions in the soluble aluminum salt solution is preferably 0.002 to 0.01 mol / L, more preferably 0.005 to 0.07 mol / L. The present invention controls the concentration of aluminum ions in the soluble aluminum salt solution within the above range, which is more conducive to obtaining uniformly distributed magnesium ions on the activated carbon.

[0057] The present invention has no particular limitation on the method of mixing the soluble aluminum salt, water and ethanol, as long as the soluble aluminum salt can be completely dissolved in water and ethanol.

[0058] After obtaining the soluble aluminum salt solution, the present invention mixes activated carbon, soluble magnesium salt, urea and the soluble aluminum salt solution and then performs impregnation to obtain a solid-liquid mixture.

[0059] In the present invention, the pore structure of the activated carbon preferably includes macropores and small pores, the pore size of the macropores is preferably 100-200 μm, more preferably 150-200 μm; the pore size of the small pores is preferably 0-10 μm, more preferably 5-10 μm.

[0060] In the present invention, the method for preparing the activated carbon preferably comprises: subjecting wood to carbonization treatment to obtain wood carbon sheets; and subjecting the wood carbon sheets to activation treatment to obtain activated carbon.

[0061] In the present invention, the wood is preferably carbonized to obtain a wood carbon sheet.

[0062] In the present invention, the wood is preferably basswood. The present invention uses basswood as a raw material, which is more conducive to obtaining activated carbon with high strength. The present invention has no special restrictions on the size of the wood, which can be adjusted according to actual needs.

[0063] In the present invention, the temperature of the carbonization treatment is preferably 800-1000°C, more preferably 1000°C; the time of the carbonization treatment is preferably 3-10h, more preferably 6-8h. In the present invention, the heating rate from room temperature to the carbonization treatment temperature is preferably 1-10°C / min, more preferably 5-6°C / min. The present invention is more conducive to controlling the pore structure of the activated carbon by controlling the parameters of the carbonization treatment within the above range, so that it forms a pore structure with macropores of 100-200μm and small pores of 0-10μm.

[0064] In the present invention, the carbonization treatment is preferably carried out in a nitrogen atmosphere. The present invention carries out the carbonization treatment in a nitrogen atmosphere, which can increase the yield of activated carbon.

[0065] The present invention has no special limitation on the carbonization treatment device, and any conventional carbonization treatment device can be used. In the present invention, the carbonization treatment device is preferably a tubular furnace.

[0066] After obtaining the wood carbon sheet, the present invention preferably performs an activation treatment on the wood carbon sheet to obtain activated carbon.

[0067] The present invention has no special limitation on the activation treatment method, and any conventional activation treatment method can be used. In an embodiment of the present invention, the activation treatment method preferably comprises: mixing the wood carbon sheet with an activator, and then calcining, washing and drying in sequence to obtain activated carbon.

[0068] In the present invention, the activating agent is preferably zinc chloride. In the present invention, the mass ratio of the wood carbon sheet to the zinc chloride during the activation treatment is 1:(1-5), more preferably 1:3. The present invention can activate the wood carbon sheet by using zinc chloride as an activating agent.

[0069] The present invention does not specifically limit the method for mixing the wood carbon sheet with the activator, as long as the zinc chloride can be fully and evenly mixed with the wood carbon sheet. In an embodiment of the present invention, the method for mixing the wood carbon sheet with the activator is preferably to immerse the wood carbon sheet in a zinc chloride solution so that the zinc chloride is fully adsorbed into the wood carbon sheet. The present invention does not specifically limit the concentration of the zinc chloride solution, and it can be adjusted according to the size of the wood carbon sheet so that the mass ratio of the wood carbon sheet to the zinc chloride can reach the above range, and the wood carbon sheet can be immersed in the zinc chloride solution.

[0070] In the present invention, the wood carbon sheet is preferably impregnated in a zinc chloride solution, and then the impregnated wood carbon sheet is dried and then calcined. In the present invention, the drying temperature is preferably 90 to 120° C., and more preferably 100° C. The present invention has no particular limitation on the drying time, and the drying time can be adjusted according to the size of the wood carbon sheet, as long as the impregnated wood is fully dried.

[0071] In the present invention, the calcination temperature is preferably 600-900°C, more preferably 800°C; the calcination time is preferably 1-5h, more preferably 2h. The present invention can fully activate by controlling the calcination temperature and time within the above ranges.

[0072] The present invention has no special limitation on the washing and drying methods, and conventional operation methods can be used to fully remove the residual zinc oxide in the calcined product. In the present invention, the washing reagent is preferably acid washing and water washing performed in sequence. In the present invention, the acid washing reagent is preferably a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is preferably 0.5 mol / L, and the water used for washing is preferably boiling water.

[0073] In the present invention, the soluble magnesium salt preferably includes magnesium nitrate, magnesium sulfate, magnesium chloride or magnesium oxalate. The present invention utilizes the above soluble magnesium salt to provide a magnesium source for MgAl-LDH.

[0074] In the present invention, the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution is 1 to 5: 1, preferably 2 to 3: 1. The present invention controls the usage of the two within the above range, and can control the molar ratio of Mg to Al in MgAl-LDH.

[0075] In the present invention, the urea can promote the formation and growth of MgAl-LDH, thereby obtaining MgAl-LDH nanomaterials.

[0076] In the present invention, the ratio of the total amount of the soluble magnesium salt and the soluble aluminum salt to the amount of urea is preferably (0.001-0.003):(0.01-0.03), more preferably 0.003:0.01. The present invention controls the amount of urea within the above range, which is more conducive to the formation of MgAl-LDH.

[0077] In the present invention, the method for mixing the activated carbon, soluble magnesium salt, urea and soluble aluminum salt solution preferably comprises: ultrasonically mixing the activated carbon and the soluble aluminum salt solution to obtain an activated carbon-aluminum salt solution; and dissolving the soluble magnesium salt and urea in the activated carbon-aluminum salt solution.

[0078] In the present invention, the activated carbon is preferably ultrasonically mixed with the soluble aluminum salt solution.

[0079] In the present invention, the ultrasonic time is preferably 10 to 60 minutes, more preferably 30 minutes. The present invention can fully adsorb aluminum ions in the pores of activated carbon through ultrasound.

[0080] After obtaining the activated carbon-aluminum salt solution, the present invention preferably dissolves the soluble magnesium salt and urea in the activated carbon-aluminum salt solution. In the present invention, the dissolution of the soluble magnesium salt and urea in the activated carbon-aluminum salt solution is preferably carried out under stirring.

[0081] In the present invention, the impregnation is preferably carried out at room temperature. The impregnation time is preferably 10 to 60 minutes, more preferably 30 minutes. In the present invention, the impregnation is preferably carried out under ultrasound. The present invention can promote the soluble magnesium salt and urea to fully enter the pore structure of the activated carbon through ultrasound.

[0082] After obtaining the solid-liquid mixture, the present invention performs a hydrothermal reaction on the solid-liquid mixture to obtain a MgAl-LDH@HPWC composite material.

[0083] In the present invention, the temperature of the hydrothermal reaction is preferably 80 to 150° C., more preferably 120° C.; the time of the hydrothermal reaction is preferably 16 to 30 hours, more preferably 24 hours. The present invention controls the temperature and time of the hydrothermal reaction within the above ranges, so that the magnesium salt and the aluminum salt can fully react to form MgAl-LDH on the activated carbon.

[0084] The present invention has no special limitation on the device for the hydrothermal reaction, and any conventional hydrothermal reaction device may be used.

[0085] The present invention preferably filters, washes and dries the system obtained after the hydrothermal reaction to obtain the MgAl-LDH@HPWC composite material. The present invention has no particular limitation on the operation methods of the filtration, washing and drying, and conventional filtration, washing and drying methods can be used to fully remove impurities in the MgAl-LDH@HPWC composite material.

[0086] After obtaining the MgAl-LDH@HPWC composite material, the present invention mixes the MgAl-LDH@HPWC composite material with ethylene glycol, an alkaline regulator, tellurium dioxide, a stabilizer and a reducing agent to perform a reduction reaction to obtain a Te nanosheet / MgAl-LDH@HPWC mixed solution.

[0087] In the present invention, the ethylene glycol is used as a solvent. The present invention has no particular limitation on the amount of the ethylene glycol used, and the amount can be adjusted to complete the reduction reaction.

[0088] In the present invention, the alkaline regulator is preferably sodium hydroxide. By adding the alkaline regulator, the reaction system can be alkaline, which is more conducive to the full reduction reaction. In the present invention, the mass ratio of the tellurium dioxide to the alkaline regulator is preferably (0.1-0.6): (0.1-0.6), and more preferably 0.3:0.6.

[0089] In the present invention, the stabilizer is preferably polyvinyl pyrrolidone. The present invention can improve the dispersibility of the product Te nanosheets by adding a stabilizer. In the present invention, the mass ratio of the tellurium dioxide to the stabilizer is preferably (0.1-0.5): (0.1-0.5), more preferably 0.3:0.2.

[0090] In the present invention, the tellurium dioxide is used as a tellurium source for forming Te nanosheets. In the present invention, the mass ratio of the MgAl-LDH@HPWC composite material to tellurium dioxide is preferably (0.01-0.05):(0.1-0.5), and more preferably 0.02:0.3. The present invention controls the amount of the two within the above range, so that the Te content in the carbon-based composite material can reach the desired range.

[0091] In the present invention, the reducing agent is preferably hydrazine hydrate. The present invention adds a reducing agent to cause a reduction reaction to obtain Te nanosheets / MgAl-LDH@HPWC. The present invention has no particular limitation on the amount of the reducing agent, which can be adjusted according to the amount of tellurium dioxide so that tellurium dioxide can fully react to form Te nanosheets.

[0092] The present invention has no particular limitation on the method for mixing the MgAl-LDH@HPWC composite material with ethylene glycol, alkaline regulator, tellurium dioxide, stabilizer and reducing agent, as long as the above components can be mixed evenly. In the present invention, the method for mixing the MgAl-LDH@HPWC composite material with ethylene glycol, alkaline regulator, tellurium dioxide, stabilizer and reducing agent preferably comprises: mixing the MgAl-LDH@HPWC composite material with ethylene glycol, alkaline regulator, tellurium dioxide and stabilizer, heating to the temperature of the reduction reaction, and then adding the reducing agent under a nitrogen atmosphere.

[0093] In the present invention, the temperature of the reduction reaction is preferably 120-200°C, more preferably 160°C; the time of the reduction reaction is preferably 30-90 min, more preferably 60 min. In the present invention, the reduction reaction is preferably carried out in a nitrogen atmosphere. The present invention can make the reduction reaction more sufficient by controlling the conditions of the reduction reaction within the above range.

[0094] After obtaining the Te nanosheet / MgAl-LDH@HPWC mixed solution, the present invention preferably mixes the Te nanosheet / MgAl-LDH@HPWC mixed solution with a soluble copper salt solution to perform a solvothermal reaction to obtain a carbon-based composite material.

[0095] In the present invention, the soluble copper salt solution is preferably a copper nitrate solution, the concentration of the copper nitrate solution is preferably 0.05 to 0.15 mol / L, more preferably 0.1 mol / L, and the solvent of the copper nitrate solution is preferably ethylene glycol.

[0096] The present invention has no special limitation on the method of mixing the Te nanosheet / MgAl-LDH@HPWC mixed solution with the soluble copper salt solution, as long as the two can be mixed evenly.

[0097] In the present invention, the temperature of the solvothermal reaction is preferably 120-200°C, more preferably 160°C; the time of the solvothermal reaction is preferably 30-90 minutes, more preferably 60 minutes. The present invention can make the reaction more complete by controlling the conditions of the solvothermal reaction within the above range.

[0098] The schematic diagram of the method for preparing the carbon-based composite material provided by the present invention is preferably as follows Figure 1 As shown. Figure 1 It can be seen that the present invention prepares three-dimensional wood activated carbon, and then obtains magnesium aluminum double hydroxide modified three-dimensional wood activated carbon (i.e., MgAl-LDH@HPWC composite material) through hydrothermal reaction, and then obtains copper telluride modified magnesium aluminum double hydroxide modified three-dimensional wood activated carbon (i.e., carbon-based composite material) through solvent thermal reaction.

[0099] The present invention also provides a device for mobile capacitive deionization coupled electrochemical denitrification, comprising a mobile electrode, a cation exchange membrane, a reaction chamber, an anion exchange membrane and a carbon-based fixed electrode which are sequentially arranged in contact;

[0100] The carbon-based fixed electrode is the carbon-based composite material described in the above technical solution or the carbon-based composite material prepared by the preparation method described in the above technical solution

[0101] A serpentine flow channel is engraved on the side of the electrode cavity of the flow electrode that contacts the cation exchange membrane; a liquid inlet and a liquid outlet are provided on the electrode cavity, and the liquid inlet and the liquid outlet are respectively arranged at two ends of the serpentine flow channel;

[0102] The reaction chamber is a silica gel plate with serpentine hollowing; the serpentine hollowing coincides with the projection of the serpentine flow channel in the electrode chamber on the cation exchange membrane; the space formed by the serpentine hollowing, the cation exchange membrane and the anion exchange membrane is a reaction chamber; a water inlet and a water outlet are provided on the reaction chamber; the water inlet is arranged at one end of the serpentine hollowing corresponding to the liquid inlet; the water outlet is arranged at one end of the serpentine hollowing corresponding to the liquid outlet; the reaction chamber includes a through hole with a nut.

[0103] like Figure 2 As shown, in the present invention, the device for mobile capacitive deionization coupled electrochemical denitrification comprises an electrode cavity, a cation exchange membrane, a reaction cavity, an anion exchange membrane and a carbon-based fixed electrode which are sequentially arranged in contact.

[0104] In the present invention, the device for flow capacitive deionization coupled electrochemical denitrification comprises a flow electrode.

[0105] In the present invention, a serpentine flow channel is engraved on the side of the electrode cavity of the flow electrode that contacts the cation exchange membrane. The present invention uses the serpentine flow channel as the flow channel of the liquid electrode material, which can make the liquid electrode material contact the cation exchange membrane and adsorb hardness interfering ions in the wastewater.

[0106] In the present invention, the length of the electrode cavity is preferably 80-200 mm, more preferably 120 mm; the width of the electrode cavity is preferably 50-120 mm, more preferably 80-100 mm; the thickness of the electrode cavity is preferably 5-15 mm, more preferably 8-10 mm. The present invention selects the size of the electrode cavity according to the amount of wastewater and the mechanical bearing capacity of the reaction device. When the size of the electrode cavity is within the above range, it is more conducive to increasing the wastewater treatment capacity.

[0107] The present invention has no special limitation on the material of the electrode cavity, and any conventional electrode cavity material can be used. In the present invention, the material of the electrode cavity is preferably graphite.

[0108] In the present invention, the depth of the serpentine flow channel is preferably 1 to 3 mm, more preferably 2 mm; the width of the serpentine flow channel is preferably 1 to 3 mm, more preferably 2 mm; the number of columns of the serpentine flow channel is preferably 15 to 35 columns, more preferably 18 to 20 columns. The present invention controls the parameters of the serpentine flow channel within the above range, which can make the cation exchange membrane and the electrode cavity have a suitable contact area, which is more conducive to increasing the treatment capacity of wastewater. In one embodiment of the present invention, the contact area between the cation exchange membrane and the serpentine flow channel of the electrode cavity is preferably 25 cm 2 .

[0109] In the present invention, the electrode cavity is provided with a liquid inlet and a liquid outlet, and the liquid inlet and the liquid outlet are respectively arranged at the two ends of the serpentine flow channel. In one embodiment of the present invention, the liquid inlet and the liquid outlet are connected to an external regeneration tank. The present invention can regenerate the liquid electrode material that adsorbs hardness ions and improve the service life of the electrode by connecting the two ends of the serpentine flow channel to the external regeneration tank.

[0110] The present invention has no special limitation on the material of the liquid-phase electrode material, and any liquid-phase electrode material of a conventional flow electrode can be used.

[0111] In the present invention, the device for mobile capacitive deionization coupled with electrochemical denitrification comprises a cation exchange membrane in contact with a side of an electrode cavity engraved with a serpentine flow channel.

[0112] The present invention has no special limitation on the material of the cation exchange membrane, and a conventional commercially available cation exchange membrane can be used. In one embodiment of the present invention, the source of the cation exchange membrane is preferably Corningwater. The present invention uses a flow electrode to enrich hardness ions in wastewater.

[0113] In the present invention, the mobile capacitive deionization coupled electrochemical denitrification device comprises a reaction chamber in contact with a cation exchange membrane.

[0114] In the present invention, the reaction chamber is a silica gel plate with serpentine hollowing. The present invention has no special limitation on the source of the silica gel plate, and any conventional silica gel plate can be used.

[0115] In the present invention, the serpentine hollowing coincides with the projection of the serpentine flow channel in the electrode cavity on the cation exchange membrane. The present invention uses the space formed by the serpentine hollowing and the cation exchange membrane and the anion exchange membrane as the reaction chamber for the wastewater to be treated.

[0116] In the present invention, the reaction chamber is provided with a water inlet and a water outlet; the water inlet is arranged at one end of the serpentine hollow corresponding to the liquid inlet; the water outlet is arranged at one end of the serpentine hollow corresponding to the liquid outlet. The present invention allows the wastewater to be treated to enter the reaction chamber through the water inlet, and allows the treated wastewater to flow out through the water outlet, so that the wastewater is circulated through the reaction chamber for treatment.

[0117] In the present invention, the wastewater in the wastewater pool enters the reaction chamber through the water inlet, undergoes flow capacitive deionization reaction in the reaction chamber, and then flows out of the reaction chamber through the water outlet and enters the wastewater pool. The deposition and blockage effect of hardness ions in the wastewater during the denitrification process is removed through the circulation process.

[0118] In the present invention, the reaction chamber includes a through hole with a nut, and the number of the through holes with a nut is preferably more than two. The present invention provides a through hole in the reaction chamber and uses a nut to control the switch of the through hole. After the nut is opened, the generated N2 can be discharged.

[0119] In the present invention, the mobile capacitive deionization coupled electrochemical denitrification device comprises an anion exchange membrane in contact with the reaction chamber.

[0120] The present invention has no special limitation on the material of the anion exchange membrane, and a conventional commercially available anion exchange membrane can be used. In one embodiment of the present invention, the source of the anion exchange membrane is preferably Corningwater. The present invention uses anion exchange membrane to enrich anions in wastewater.

[0121] In the present invention, the device for mobile capacitive deionization coupled with electrochemical denitrification comprises a carbon-based fixed electrode in contact with an anion exchange membrane.

[0122] In the present invention, the carbon-based fixed electrode is the carbon-based composite material described in the above technical solution or the carbon-based composite material prepared by the preparation method described in the above technical solution.

[0123] The carbon-based fixed electrode is preferably a carbon-based fixed electrode formed by coating a carbon-based composite material powder on a current collector or a self-supporting carbon-based composite material.

[0124] In the present invention, the current collector is preferably a graphite plate.

[0125] When the device provided by the present invention treats wastewater, the electrode cavity is first used as the cathode and the carbon-based fixed electrode is used as the anode to perform the FCDI process. During this process, the wastewater in the reaction cavity contacts the cation exchange membrane and the anion exchange membrane, so that the ammonia nitrogen and hardness ions (such as Ca 2+ Mg 2+ etc.) are adsorbed by the electrode material filled in the serpentine flow channel of the electrode cavity through the cation exchange membrane, so as to remove the deposition and blockage of hardness ions in the wastewater during the denitrification process; at the same time, the interference of competing anions is removed by the selective adsorption of carbon-based materials, so that nitrate ions in the wastewater are enriched at the anode; after completing the FCDI process, by switching the positive and negative poles of the power supply, the mobile electrode is used as the anode and the fixed electrode is used as the cathode, and the NO3RR process is carried out. In this process, the enriched anions are reduced to N2, thereby being able to efficiently achieve harmless conversion of nitric nitrogen; the present invention includes a through hole with a nut on the reaction chamber, and the nut can control the switch of the through hole. When gas is generated, opening the nut can discharge the generated gas.

[0126] The present invention also provides a method for flow capacitor deionization coupled electrochemical denitrification, using the above-mentioned device, comprising the following steps:

[0127] Passing the liquid electrode material into the serpentine flow channel of the electrode cavity through the liquid inlet to form a flow electrode;

[0128] The mobile electrode is connected to the negative electrode of the external power supply, and the fixed electrode is connected to the positive electrode of the external power supply to obtain a FCDI system;

[0129] The wastewater to be treated is introduced into the reaction chamber from the water inlet and flows out from the water outlet, and the FCDI process is circulated until the total nitrogen content in the treated wastewater reaches the standard, then the introduction of the wastewater to be treated is stopped, and the remaining wastewater in the reaction chamber is retained;

[0130] Switching the positive and negative electrodes of the external power supply, connecting the mobile electrode to the positive electrode of the external power supply and connecting the fixed electrode to the negative electrode of the external power supply, thereby obtaining a NO3RR system;

[0131] The through hole of the reaction chamber is opened, and the remaining wastewater is subjected to an electrochemical reduction reaction in the NO3RR system until no gas is generated.

[0132] The present invention passes the liquid electrode material into the serpentine flow channel of the electrode cavity through the liquid inlet to form a flow electrode.

[0133] In the present invention, the liquid-phase electrode material is an activated carbon suspension. In one embodiment of the present invention, the activated carbon suspension is obtained by dispersing activated carbon in a 0.1 mol / L NaCl solution, and the mass of the activated carbon accounts for 5% of the mass of the NaCl solution. In one embodiment of the present invention, the liquid-phase electrode material is preferably an activated carbon suspension, and the activated carbon suspension is obtained by dispersing activated carbon in a 0.1 mol / L NaCl solution, and the mass of the activated carbon accounts for 5% of the mass of the NaCl solution.

[0134] The present invention does not specifically limit the method of passing the liquid electrode material through the liquid inlet into the serpentine flow channel of the electrode cavity, and a conventional pumping device can be used. In the present invention, the pumping device is preferably a peristaltic pump. The present invention uses a pumping device to make the liquid electrode material flow out of the liquid outlet through the serpentine flow channel, and then regenerates the liquid electrode material in the regeneration tank, thereby extending the service life of the liquid electrode material.

[0135] In the present invention, the flow rate of the liquid electrode material into the electrode cavity through the liquid inlet is preferably 3 to 15 mL min -1 , more preferably 5 mL min -1 The present invention limits the flow rate of the liquid electrode material to the above range to prevent the AC from being saturated due to too low a flow rate and reducing the overall adsorption capacity; it can also prevent the AC from being not fully utilized due to too high a flow rate.

[0136] After forming the mobile electrode, the present invention connects the mobile electrode to the negative electrode of the external power supply, and connects the fixed electrode to the positive electrode of the external power supply to obtain the FCDI system. The present invention has no special limitation on the method of connecting the mobile electrode to the negative electrode of the external power supply and connecting the fixed electrode to the positive electrode of the external power supply. The conventional connection method can make the mobile electrode a cathode and the fixed electrode an anode.

[0137] After obtaining the FCDI system, the present invention allows the wastewater to be treated to be introduced into the reaction chamber from the water inlet and flow out through the water outlet, and the FCDI process is circulated. When the total nitrogen content in the treated wastewater reaches the standard, the introduction of the wastewater to be treated is stopped, and the remaining wastewater in the reaction chamber is retained.

[0138] In the present invention, the flow rate of the wastewater to be treated from the water inlet into the reaction chamber is preferably 10 to 20 mL min -1 , more preferably 12 to 15 mL / min -1The present invention controls the flow rate of the wastewater to be treated from the water inlet into the reaction chamber within the above range, which is more conducive to improving the effect of treating the wastewater.

[0139] In the present invention, the voltage of the FCDI process is preferably +0.8 to +2V, more preferably +1.2V; the time of the FCDI process is preferably 10 to 60 minutes, more preferably 30 minutes. The present invention is more conducive to improving the effect of treating wastewater by carrying out the FCDI process under the above parameters.

[0140] In the present invention, the total nitrogen content in the treated wastewater is preferably <7 mg / L, reaching the standard for stopping the FCDI process. The present invention cyclically performs the FCDI process until the total nitrogen content in the treated wastewater reaches the above range, and then stops the FCDI process.

[0141] After obtaining the wastewater with cations removed, the present invention switches the positive and negative poles of the external power supply, connects the mobile electrode to the positive pole of the external power supply, connects the fixed electrode to the negative pole of the external power supply, makes the mobile electrode serve as the anode, and the fixed electrode serves as the cathode, to obtain the NO3RR system.

[0142] After obtaining the NO3RR system, the present invention opens the through hole of the reaction chamber, and performs an electrochemical reduction reaction on the remaining wastewater in the NO3RR system until no gas is generated, thereby obtaining purified water.

[0143] The present invention has no special limitation on the method of passing the decationized wastewater into the NO3RR system, and it can be adjusted as needed. In the present invention, the decationized wastewater is retained in the reaction chamber, and the present invention removes the anion NO3 in the decationized wastewater retained in the reaction chamber through the NO3RR process. - , react to form N2, until no more gas is produced, to obtain purified water, and the N2 is discharged through the through hole with a nut on the reaction chamber.

[0144] In the present invention, the current density of the electrochemical reduction reaction is preferably 10 to 50 mA cm -2 , more preferably 30mAcm -2 .

[0145] The principle schematic diagram of the method for mobile capacitor deionization coupled electrochemical denitrification provided by the present invention is preferably as follows Figure 3 As shown. Figure 3 It can be seen that the present invention uses the FCDI process to remove hardness ions (i.e., desalination); then uses the NO3RR process to remove the enriched NO3 - Electrochemical reduction at the cathode generates harmless N2 emissions, achieving denitrification, and thus enabling efficient and harmless conversion of nitrate-nitrogen.

[0146] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0147] Example 1

[0148] A carbon-based composite material, the carbon-based composite material is composed of activated carbon and a Cu2Te / MgAl-LDH heterojunction supported on the activated carbon; the pore size of the macropores of the activated carbon is in the range of 100 to 200 μm; the pore size of the micropores of the activated carbon is in the range of 5 to 10 μm;

[0149] The molar ratio of Mg to Al in the Cu2Te / MgAl-LDH heterojunction is 2:1;

[0150] The mass of the Cu2Te / MgAl-LDH heterojunction accounts for 1% of the mass of the carbon-based composite material;

[0151] The mass ratio of Cu2Te to MgAl-LDH in the Cu2Te / MgAl-LDH heterojunction is 1:2;

[0152] The preparation method of the above carbon-based composite material is:

[0153] (1) 0.3750 g of aluminum nitrate, 40 mL of deionized water, and 10 mL of ethanol were mixed to obtain an aluminum nitrate solution;

[0154] (2) Place a 4.0 cm × 6.0 cm × 0.1 cm basswood piece in a tubular furnace in a N2 atmosphere, heat it to 1000°C at a heating rate of 5°C / min, and calcine it for 6 hours to obtain a wood carbon piece; soak the wood carbon piece in a ZnCl2 solution (the mass ratio of the wood carbon piece to ZnCl2 is 1:3) overnight to completely infiltrate the wood carbon piece; then dry it in air at 100°C for at least 12 hours; place the obtained product in a tubular furnace in a N2 atmosphere and activate it at 800°C for 2 hours, immerse the activated carbon piece in a 0.5 mol / L HCl solution to remove ZnO residues, and then wash it with boiling water until it is neutral to obtain activated carbon, referred to as HPWC;

[0155] 0.2478 g of HPWC was immersed in an aluminum nitrate solution and ultrasonically vibrated for 30 minutes, magnesium nitrate and urea were added to the solution obtained by the ultrasonic vibration, stirred and dissolved, and then immersed under ultrasound for 30 minutes to obtain a solid-liquid mixture; wherein the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution was 2:1;

[0156] (3) placing the solid-liquid mixture obtained in step (2) in a hydrothermal reactor, performing a hydrothermal reaction at 120° C. for 24 h, washing, and drying at 100° C. for 12 h to obtain a MgAl-LDH@HPWC composite material;

[0157] (4) 0.2502 g of the MgAl-LDH@HPWC composite material obtained in step (3) was mixed with 20 mL of ethylene glycol, 0.6 g of sodium hydroxide, 0.3 g of tellurium dioxide and 0.2 g of polyvinyl pyrrolidone, and then heated to 160° C., and then 0.7 mL of hydrazine hydrate (AR) was added, and a reduction reaction was carried out at 160° C. for 1 h to obtain a Te nanosheet / MgAl-LDH@HPWC mixed solution;

[0158] (5) The Te nanosheet / MgAl-LDH@HPWC mixed solution obtained in step (4) is mixed with a 0.1 mol / L copper nitrate solution (the solvent is ethylene glycol), reacted at 160° C. for 1 h, and washed and dried to obtain a carbon-based composite material, referred to as CLC.

[0159] Example 2

[0160] The difference from Example 1 is that in the preparation method of the carbon-based composite material, the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution in step (2) is 1:1, and the remaining steps are the same as in Example 1.

[0161] Example 3

[0162] The difference from Example 1 is that in the preparation method of the carbon-based composite material, the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution in step (2) is 3:1, and the remaining steps are the same as in Example 1.

[0163] Example 4

[0164] The difference from Example 1 is that in the preparation method of the carbon-based composite material, the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution in step (2) is 4:1, and the remaining steps are the same as in Example 1.

[0165] Example 5

[0166] The difference from Example 1 is that in the preparation method of the carbon-based composite material, the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution in step (2) is 5:1, and the remaining steps are the same as in Example 1.

[0167] Test Example 1

[0168] The XRD patterns of HPWC prepared in Examples 1 to 5 and MgAl-LDH@HPWC with different Mg and Al molar ratios are shown in Figure 2. Figure 4As shown. Figure 4 The XRD diffraction patterns of different interlayer spacings are calculated, as shown in Table 1:

[0169] Table 1 Interlayer spacing of MgAl-LDH@HPWC prepared in Examples 1 to 5

[0170]

[0171]

[0172] It can be seen from Table 1 that the interlayer spacing of MgAl-LDH@HPWC prepared in Example 1 is the best and is more suitable as an electrode material.

[0173] The SEM images of MgAl-LDH@HPWC and HPWC prepared in Example 1 are as follows: Figure 5 As shown. Figure 5 In the figure, a1~a3 are top view SEM images of MgAl-LDH@HPWC at different scales; b1~b3 are cross-sectional SEM images of MgAl-LDH@HPWC at different scales; c1~c3 are top view SEM images of HPWC at different scales; d1~d3 are cross-sectional SEM images of HPWC at different scales. Figure 5 It can be seen that the MgAl-LDH@HPWC prepared by the present invention has an open through-type HPWC (uniformly distributed macropores (100-200 μm) and micropores (0-10 μm)). When it is used as a carbon-based fixed electrode, it can reduce NO3 - The diffusion distance on the cathode reduces the resistance of water flow and increases the NO3 - Effective contact with the cathode offsets the hindrance of electrostatic repulsion.

[0174] The HRTEM image of MgAl-LDH@HPWC prepared in Example 1 is as follows: Figure 6 As shown. Figure 6 In the figure, (a) is a low-magnification TEM image of MgAl-LDH@HPWC, (b) is a HRTEM image of MgAl-LDH nanosheets, (c) is a SAED spectrum of MgAl-LDH nanosheets, and (d) is the EDS element mapping of Mg, Al, O, and C corresponding to MgAl-LDH / HPWC. Figure 6 a It can be seen that the ultrathin LDH nanosheets grown on wood activated carbon present a hexagonal structure, which is due to the fact that LDH belongs to the hexagonal crystal system. Figure 6 b At a higher magnification, lattice fringes with interplanar spacings of 0.157 nm and 0.272 nm corresponding to the (012) and (110) planes of the LDH nanosheets are shown. Figure 6c shows that the SAED spectrum of LDH nanosheets is a ring-shaped distribution with obvious bright spots, which proves the crystalline structure of LDH nanosheets. The corresponding (003), (012) and (110) crystal planes are consistent with the XRD data. Figure 6 The EDS elemental mapping spectrum of d shows the uniform distribution of Mg and Al on the HPWC substrate (containing C and O), further proving that the LDH nanosheets are successfully loaded on the HPWC surface.

[0175] Example 6

[0176] like Figure 2 As shown, the mobile capacitive deionization coupled electrochemical denitrification device of this embodiment includes a mobile electrode, a cation exchange membrane, a reaction chamber, an anion exchange membrane and a carbon-based fixed electrode that are sequentially arranged in contact;

[0177] The cation exchange membrane and anion exchange membrane are both from Corningwater;

[0178] The carbon-based fixed electrode is the carbon-based composite material prepared in Example 1;

[0179] A serpentine flow channel is engraved on the side of the electrode cavity of the flow electrode in contact with the cation exchange membrane; the electrode cavity is a graphite plate with a length of 120 mm, a width of 80 mm, and a thickness of 8 mm; the depth of the serpentine flow channel is 2 mm; the width of the serpentine flow channel is 2 mm; the number of columns of the serpentine flow channel is 18; the serpentine flow channel serves as a flow channel for a liquid electrode material, the liquid electrode material is an activated carbon suspension, the activated carbon suspension is obtained by dispersing activated carbon in a 0.1 mol / L NaCl solution, and the mass of the activated carbon accounts for 5% of the mass of the NaCl solution;

[0180] The electrode cavity is provided with a liquid inlet and a liquid outlet, and the liquid inlet and the liquid outlet are respectively arranged at two ends of the serpentine flow channel; the liquid inlet and the liquid outlet are connected to an external regeneration tank;

[0181] The reaction cavity is a silica gel plate with serpentine hollowing; the serpentine hollowing coincides with the projection of the serpentine flow channel in the electrode cavity on the cation exchange membrane; the space formed by the serpentine hollowing, the cation exchange membrane and the anion exchange membrane is a reaction chamber; a water inlet and a water outlet are provided on the reaction cavity; the water inlet is arranged at the end of the serpentine hollowing corresponding to the liquid inlet; the water outlet is arranged at the end of the serpentine hollowing corresponding to the liquid outlet; the water inlet and the water outlet are connected to an external circulation pool; and there are two through holes with nuts on the reaction chamber.

[0182] Example 7

[0183] 100 mL of simulated seawater aquaculture circulating water was prepared in advance as wastewater to be treated, with an initial Cl- concentration of 19000 mg L -1 , regulating NO3 - Initial concentration (10 mg L -1 , 20mg L -1 , 50mg L -1 , 100mg L -1 and 200 mg L -1 ).

[0184] A method for flow capacitor deionization coupled with electrochemical denitrification, using the device described in Example 6, the steps are:

[0185] The liquid electrode material is introduced into the serpentine flow channel of the electrode cavity through the liquid inlet at a flow rate of 5 mL / min by a peristaltic pump to form a flow electrode; wherein the liquid electrode material is an activated carbon suspension obtained by dispersing activated carbon in a 0.1 mol / L NaCl solution, and the mass of the activated carbon accounts for 5% of the mass of the NaCl solution;

[0186] The mobile electrode was connected to the negative electrode of the external power supply, and the fixed electrode was connected to the positive electrode of the external power supply at a voltage of 1.2 V to obtain the FCDI system;

[0187] NO3 - The initial concentration was 10 mg L -1 The wastewater to be treated is introduced into the reaction chamber from the water inlet at a flow rate of 12 mL / min and flows out from the water outlet. The FCDI process is circulated for 20 min. When the total nitrogen content in the treated wastewater reaches the standard (concentration < 7 mg / L), the introduction of the wastewater to be treated is stopped and the remaining wastewater in the reaction chamber is retained.

[0188] Switching the positive and negative electrodes of the external power supply, connecting the mobile electrode to the positive electrode of the external power supply and connecting the fixed electrode to the negative electrode of the external power supply, thereby obtaining a NO3RR system;

[0189] Open the reaction chamber through hole, and put the remaining wastewater into the NO3RR system, controlling the current density to 30 mA cm -2 , run for 30 min to carry out the electrochemical reduction reaction until no more gas is produced.

[0190] The method of this embodiment is denoted as FNR-CLC.

[0191] Example 8

[0192] The difference from Example 7 is that NO3 - The initial concentration was 20 mg L -1 , the remaining steps are the same as Example 7.

[0193] Example 9

[0194] The difference from Example 7 is that NO3 - The initial concentration was 50 mg L -1 , the remaining steps are the same as Example 7.

[0195] Example 10

[0196] The difference from Example 7 is that NO3 - The initial concentration was 100 mg L -1 , the remaining steps are the same as Example 7.

[0197] Embodiment 11

[0198] The difference from Example 7 is that NO3 - The initial concentration was 200 mg L -1 , the remaining steps are the same as Example 7.

[0199] Comparative Example 1

[0200] The difference from Example 7 is that HPWC is used as the fixed electrode, and the remaining steps are the same as those of Example 7. The method of this comparative example is denoted as FNR.

[0201] Comparative Example 2

[0202] The difference from Comparative Example 1 is that NO3 - The initial concentration was 20 mg L -1 , the remaining steps are the same as those in Comparative Example 1.

[0203] Comparative Example 3

[0204] The difference from Comparative Example 1 is that NO3 - The initial concentration was 50 mg L -1 , the remaining steps are the same as those in Comparative Example 1.

[0205] Comparative Example 4

[0206] The difference from Comparative Example 1 is that NO3 - The initial concentration was 100 mg L -1 , the remaining steps are the same as those in Comparative Example 1.

[0207] Comparative Example 5

[0208] The difference from Comparative Example 1 is that NO3 - The initial concentration was 200 mg L -1 , the remaining steps are the same as those in Comparative Example 1.

[0209] Comparative Example 6

[0210] A method for flow capacitor deionization coupled with electrochemical denitrification, using the device described in Example 6, the steps are:

[0211] The mobile electrode is connected to the positive electrode of the external power source, and the fixed electrode is connected to the negative electrode of the external power source to obtain a NO3RR system;

[0212] NO3 - The initial concentration was 10 mg L -1 The wastewater to be treated was passed into the NO3RR system, and the current density was controlled at 30 mA cm -2 , run for 30 minutes, carry out electrochemical reduction reaction, and obtain purified water.

[0213] The method of this embodiment is denoted as NR.

[0214] Comparative Example 7

[0215] The difference from Comparative Example 6 is that NO3 - The initial concentration was 20 mg L -1 , the remaining steps are the same as those in Comparative Example 6.

[0216] Comparative Example 8

[0217] The difference from Comparative Example 6 is that NO3 - The initial concentration was 50 mg L -1 , the remaining steps are the same as those in Comparative Example 6.

[0218] Comparative Example 9

[0219] The difference from Comparative Example 6 is that NO3 - The initial concentration was 100 mg L -1 , the remaining steps are the same as those in Comparative Example 6.

[0220] Comparative Example 10

[0221] The difference from Comparative Example 6 is that NO3 - The initial concentration was 200 mg L -1 , the remaining steps are the same as those in Comparative Example 6.

[0222] Test Example 2

[0223] The purified water obtained in Examples 7 to 11 and Comparative Examples 1 to 10 was respectively subjected to UV-visible absorption spectroscopy to determine NO3 - and NO2 - The concentration of nitrogen and total nitrogen (TN) were determined by Nessler reagent and alkaline potassium persulfate digestion spectrophotometry, respectively, and the yield of N2 was calculated. - The removal rate of Figure 7 As shown, the selectivity of N2 is Figure 8 As shown. Figure 7 and Figure 8 It can be seen that using the FNR-CLC method, at different initial concentrations, NO3 - The removal rate can be maintained above 93%, and the N2 selectivity can be maintained above 96%, which is much better than the control example.

[0224] From the above results, it can be seen that the device provided by the present invention can significantly improve the effect of harmless conversion of nitrate nitrogen. This is because the device provided by the present invention uses FCDI to adsorb hardness ions (Ca 2+ Mg 2+ etc.), solve the electrode blockage problem in the electrochemical reduction process, and use the anode to adsorb NO3 - , enriched NO3 - It can improve the efficiency of electrochemical reduction of nitrate nitrogen; the constructed transition metal telluride modified double metal hydroxide modified three-dimensional biochar composite material can improve the final product N2 selectivity, NO3 - Adsorption selectivity and resistance to electrostatic repulsion.

[0225] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A carbon-based composite material comprising activated carbon and a Cu2Te / MgAl-LDH heterojunction supported on the activated carbon, wherein the molar ratio of Mg to Al in the Cu2Te / MgAl-LDH heterojunction is 1 to 5:

1.

2. The carbon-based composite material according to claim 1, characterized in that: The mass of the Cu2Te / MgAl-LDH heterojunction accounts for 1-5% of the mass of the carbon-based composite material.

3. The carbon-based composite material according to claim 1, characterized in that: The mass ratio of Cu2Te to MgAl-LDH in the Cu2Te / MgAl-LDH heterojunction is (1-2):(1-5).

4. The method for preparing the carbon-based composite material according to any one of claims 1 to 3, comprising the following steps: (1) mixing a soluble aluminum salt, water and ethanol to obtain a soluble aluminum salt solution; (2) mixing activated carbon, soluble magnesium salt, urea and the soluble aluminum salt solution obtained in step (1) and then impregnating the mixture to obtain a solid-liquid mixture; the molar ratio of the soluble magnesium salt to the soluble aluminum salt in the soluble aluminum salt solution is 1 to 5:1; (3) subjecting the solid-liquid mixture obtained in step (2) to a hydrothermal reaction to obtain a MgAl-LDH@HPWC composite material; (4) mixing the MgAl-LDH@HPWC composite material obtained in step (3) with ethylene glycol, an alkaline regulator, tellurium dioxide, a stabilizer and a reducing agent, and performing a reduction reaction to obtain a Te nanosheet / MgAl-LDH@HPWC mixed solution; (5) The Te nanosheet / MgAl-LDH@HPWC mixed solution obtained in step (4) is mixed with a soluble copper salt solution to perform a solvothermal reaction to obtain a carbon-based composite material.

5. The preparation method according to claim 4, characterized in that: The temperature of the hydrothermal reaction in step (3) is 80 to 150° C.; the time of the hydrothermal reaction is 16 to 30 hours.

6. The preparation method according to claim 4, characterized in that: The temperature of the reduction reaction in step (4) and the solvothermal reaction in step (5) are independently 120 to 200° C.; the time of the reduction reaction and the solvothermal reaction are independently 30 to 90 minutes.

7. A device for flow capacitive deionization coupled with electrochemical denitrification, comprising a flow electrode, a cation exchange membrane, a reaction chamber, an anion exchange membrane and a carbon-based fixed electrode arranged in contact with each other in sequence; The carbon-based fixed electrode is a carbon-based composite material according to any one of claims 1 to 3 or a carbon-based composite material prepared by the preparation method according to any one of claims 4 to 6; A serpentine flow channel is engraved on the side of the electrode cavity of the flow electrode that contacts the cation exchange membrane; a liquid inlet and a liquid outlet are provided on the electrode cavity, and the liquid inlet and the liquid outlet are respectively arranged at two ends of the serpentine flow channel; The reaction cavity is a silica gel plate with serpentine hollowing; the serpentine hollowing coincides with the projection of the serpentine flow channel in the electrode cavity on the cation exchange membrane; the space formed by the serpentine hollowing, the cation exchange membrane and the anion exchange membrane is a reaction chamber; a water inlet and a water outlet are provided on the reaction cavity; the water inlet is arranged at one end of the serpentine hollowing corresponding to the liquid inlet; the water outlet is arranged at one end of the serpentine hollowing corresponding to the liquid outlet; the reaction chamber includes a through hole with a nut.

8. The device for mobile capacitive deionization coupled electrochemical denitrification according to claim 7, characterized in that: The length of the electrode cavity is 80-200 mm, the width of the electrode cavity is 50-120 mm, and the thickness of the electrode cavity is 5-15 mm.

9. The device for mobile capacitive deionization coupled electrochemical denitrification according to claim 7, characterized in that: The depth of the serpentine flow channel is 1 to 3 mm, the width of the serpentine flow channel is 1 to 3 mm, and the number of columns of the serpentine flow channel is 15 to 35.

10. A method for flow capacitive deionization coupled electrochemical denitrification, using the device according to any one of claims 7 to 9, comprising the following steps: Passing the liquid electrode material into the serpentine flow channel of the electrode cavity through the liquid inlet to form a flow electrode; The mobile electrode is connected to the negative electrode of the external power supply, and the fixed electrode is connected to the positive electrode of the external power supply to obtain a FCDI system; The wastewater to be treated is introduced into the reaction chamber from the water inlet and flows out from the water outlet, and the FCDI process is circulated. When the total nitrogen content in the treated wastewater reaches the standard, the introduction of the wastewater to be treated is stopped, and the remaining wastewater in the reaction chamber is retained; Switching the positive and negative electrodes of the external power supply, connecting the mobile electrode to the positive electrode of the external power supply and connecting the fixed electrode to the negative electrode of the external power supply, thereby obtaining a NO3RR system; The through hole of the reaction chamber is opened, and the remaining wastewater is subjected to an electrochemical reduction reaction in the NO3RR system until no gas is generated.

Citation Information

Patent Citations

  • Composite cathode active material, cathode and lithium battery including the composite cathode active material and method of preparing the composite cathode active material

    CN107507973A

  • FCDI device for enhancing trace ion trapping, based on ion exchange resin, and application thereof

    CN107585835A